Claims and demonstrations of understanding in whole class interactions - Ingram, J; Andrews, N (Freudenthal Group, 2020)
One aim of teaching mathematics is to develop students’ understanding of mathematics. In this paper we examine how teachers and students do understanding in interaction, and how this understanding is handled interactively during whole class interactions. Taking a Conversation Analytic approach, we look at interactions between teachers and students where there is claim of understanding and where there is a demonstration of understanding. We show how these two situations are handled differently, by the teacher and the students, with only the latter situation being concerned with students’ understanding.